Can Natural Structural Analogues of Antimicrobials be Repurposed as External Use Disinfectants? A Small Scale Industry’s Experience in India During Pandemics - Rao, JR (British Journal of Healthcare and Medical Research, 2022)
This opinion article highlights the experience of a small group of textile entrepreneurs in India despite the economic downturn during the pandemic crisis and diversified to a small scale healthcare industry. By not only having innovated a way out of their set-backs, but also utilising a proof of concept industry-led study, they have repurposed macromolecular natural product structural analogues for external use applications such as protective antimicrobial coating for domestic and healthcare fabric laundering, and as disinfectant in places with a heavy footfall (e.g. mass / rapid transport systems, hospitality sector) in developing nations. Furthermore, natural antimicrobial analogues supplied at nanomolar dosage, this prototype product adds no burden to either environmental toxicity or antimicrobial resistance. A collaborative interplay of the industry with academia and pharmaceutical researchers would heighten the science of this industries unique approach of a different kind of ‘ drug repurposing’ to underpin a practical working solution for long-term disinfection beyond the contagion pandemics to both public and healthcare utilities in economically challenged developing nations.